2020
DOI: 10.3389/fmicb.2020.596352
|View full text |Cite
|
Sign up to set email alerts
|

Vertically Transmitted Gut Bacteria and Nutrition Influence the Immunity and Fitness of Bactrocera dorsalis Larvae

Abstract: Symbiotic bacterial communities that colonize the digestive tract of tephritid fruit flies interact with nutrient intake to improve the flies' fitness and immunity. Some bacterial species consistently inhabit the tephritid guts and are transmitted to the next generation vertically. These species contribute significantly to some aspects of their host's physiology. In the current study, we examined the role of four vertically transmitted bacteria (Citrobacter, Enterobacter, Klebsiella, and Providencia) on the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 93 publications
0
16
0
Order By: Relevance
“…There may be an association between the symbiont acquisition or transmission and the nature of the interactions between insects and symbionts. It is usual for female germline transmission to occur vertically through the female germline as with primary mutualists, for example, those present in aphids and weevils ( Caspi-Fluger et al, 2012 ; Douglas, 2015 ; Hassan et al, 2020 ). It is common for environmental microorganisms to be transmitted across internal organs, some of which can form secondary symbioses without specialized organs.…”
Section: Interaction Of Insect and Their Related Microbiotamentioning
confidence: 99%
“…There may be an association between the symbiont acquisition or transmission and the nature of the interactions between insects and symbionts. It is usual for female germline transmission to occur vertically through the female germline as with primary mutualists, for example, those present in aphids and weevils ( Caspi-Fluger et al, 2012 ; Douglas, 2015 ; Hassan et al, 2020 ). It is common for environmental microorganisms to be transmitted across internal organs, some of which can form secondary symbioses without specialized organs.…”
Section: Interaction Of Insect and Their Related Microbiotamentioning
confidence: 99%
“…Reports have also shown that folic acid can be synthesized by the intestinal microflora in animals (Hanson and Gregory, 2011). These reports provide a wealth of genetic information for our (Hassan et al, 2020). However, insects have an effective gut defense system that maintains self-immunity, thereby preserving the balance among microorganisms in the gut and stabilizing the diversity in gut symbiotic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Immunity is important for insects. Both diet and vertically transmitted bacteria can influence the fitness and immunity of B. dorsalis ( Hassan et al, 2020 ). However, insects have an effective gut defense system that maintains self-immunity, thereby preserving the balance among microorganisms in the gut and stabilizing the diversity in gut symbiotic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, nutrition is essential to pathogens resistance in insects 42,43,44 . Gomulski et al 45 , suggested that the abundance of immune gene transcripts might be related to the nature of the food sources within C. capitata.…”
Section: Discussionmentioning
confidence: 99%